Geochemistry and Depositional Conditions of the Cretaceous Oceanic Red Beds (CORBs) within the Shiranish Formation in North of Iraq - Jamal Ahmed, Mohammed; Yousif Tamar-Agha, Mazin; Abbas Alwan, Thamer (Iraqi Journal of Science, 2021)
Upper Cretaceous Oceanic Red Beds (CORBs) are pelagic sediment deposits that deposited in the Upper Cretaceous basin, with widespread in part of the world as well as in Iraq. This research investigates the deposition of cyclic marl and marly limestone CORBs of six selected sections at the active southern margin of the Tethys during the Late Campanian - Maastrichtian with petrography, microfacies, and depositional environment.The measurement of carbonate content (CaCO3 %) in the rocks, 180 samples of all the geological sections were studied twice for each sample and the average readings were taken.This examination proved the following major oxides wt. % concentrations domination SiO2, CaO, Al2 O3 and Fe2O3 with average values of 33.10, 29.63, 5.10 and 3.67 respectively, with following minor elements ppm concentrations dominance Sr, Ni, V, Zn, Cu, Zr and Co with average values of 498.4, 257.6, 67.8, 38.2, 34.3, 25.5 and 20.4 respectively. Also this group of ratios K2O/Al2O3, SiO2, Al2O3/TiO2, Ni/Co, V/Cr, Cu/Zn, Cr/Ni, V/Ni, and V/ (V+Ni) is used as an index of paleo oxygenation conditions, these ratios proved the oxidizing environments for the rock samples in the present studyThe expense of the organic matter content (TOC) has shown low content of TOC % in most studied samples, with ranges values of 0.27 in all beds, 0.18 in only red marl beds, 0.29 only non-red marl beds, 0.20 in only red marly limestone beds, 0.36 only non-red marly limestone beds .The Shiranish Formation (Late Campanian-Early Mastrichtian), composed of marl and marly limestone, rhythmically laminated. Relatively low contents of organic matter and the containing of some redox-sensitive trace elements support the interpretation of oxic bottom water conditions during the deposition of this formation, consisting of light grey, reddish, brownish, and pinkish laminated calcareous marl and marly limestone, is characterized by low TOC contents. The C13 and O18 values are indicate upon the diagenetic affective due to burial, and it means a detrital origin that may reflect local uplift and variations in weathering processes in the adjacent continental areas.